2013
DOI: 10.1177/0040517513478481
|View full text |Cite
|
Sign up to set email alerts
|

Potential of visible and near infrared spectroscopy in the determination of instrumental leaf grade in lint cottons

Abstract: Existence of non-lint materials (or botanic trash) within commercial cotton bales degrades their market value, requires a further cleaning process, and compromises finished product quality. To meet the challenge of assessing the trash content, a number of approaches have been in practice. In the US, one term to assess the degree of trash amount is leaf grade, which was originally determined by qualified US Department of Agriculture's AMS cotton classers via a visual inspection procedure. Recently, the AMS has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Liu et al attempted classification of seven leaf categories of cotton with a research grade spectrometer [ 7 ]. Classification models were developed by employing the soft independent modeling of class analogy (SIMCA) and principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al attempted classification of seven leaf categories of cotton with a research grade spectrometer [ 7 ]. Classification models were developed by employing the soft independent modeling of class analogy (SIMCA) and principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…that represent the most common variations to all spectral data. 19,20 The correlations among samples (or spectra) are indicated by their scores (or projections) on new PCs.…”
mentioning
confidence: 99%
“…Because of the heterogeneous distribution of trash type, density, and particle size, it is a challenge to link the trash amount from either type of two trash measurements with NIR spectra at satisfactory level, as revealed by relatively low NIR model performance for referenced SA and HVI TM trash indices [11,12]. As an alternative to overcome the challenge in NIR prediction of trash contents, sevenclass SIMCA/PCA (soft independent modeling of class analogy / principal component analysis) classification models in different visible/NIR spectral regions were developed to optimize the identification efficiency of cotton samples with various leaf grade categories [18]. It was observed that using the discrimination model in the 1105-1700 nm NIR regions could distinguish one class of leaf grade fibers from other six groups at a satisfactory level of ~ 95.0%.…”
Section: Corrected Predictionsmentioning
confidence: 99%
“…As a comparison, the true reference values of individual trash components in regular cottons were extremely difficult to acquire, mostly due to either current-in-use trash protocols cannot provide such information or it is labor intensive to amass different types and sizes of trash manually. In this study, lint cotton samples with various instrumental leaf grades were used, since the instrumental leaf grade was determined by an equation that utilizes HVI TM trash readings of percent area and particle count on a sample's surface [18] and so that the magnitude of instrument leaf grade should be proportional to trash level in a sample; unfortunately, present HVI TM leaf grade measurement cannot provide the trash type, such as leaf trash and non leaf trash. The accumulated knowledge could be of value as a rapid analytical tool to cotton breeders for cotton variety enhancement and also to cotton ginning engineers for trash-removal cleaning device improvement.…”
Section: Introductionmentioning
confidence: 99%